Influence of hydrocracking and ionic liquid pretreatments on composition and properties of Arabidopsis thaliana wild type and CAD mutant lignins. (June 2020) - Jacquet, Nicolas; Eudes, Aymerick; Dutta, Tanmoy; Kim, Kwang Ho; Bouxin, Florent; Benites, Veronica; Baidoo, Edward; Singh, Seema; Simmons, Blake; Loqué, Dominique; Richel, Aurore
Abstract: Lignin is the primary contributor to the high cost of biofuel-production from lignocellulosic biomass. In order to study lignin removal and the release of aromatic monomers, we applied hydrocracking and ionic liquid pretreatments on Arabidopsis thaliana biomass from both wild type (WT) and a mutant ( CAD cxd ) defective in two cinnamyl alcohol dehydrogenase genes involved in the lignin biosynthetic pathway. For Arabidopsis WT, our results highlight that pretreatments reduce average molecular weight of lignin by about 65% and decrease the content of β-O-4 linkages between lignin monomers. For Arabidopsis CAD mutant, an opposite effect is evidenced. Fewer differences were observed on depolymerization and molecular structure of lignin, which indicates that (8-O-4), (8-5), and (8-8) linkages observed in CAD mutant make lignin more resilient to pretreatment than wild-type lignin. Finally, our study shows the potential of hydrocracking pretreatment technology for extracting valuable aldehyde monomers such as vanillin and syringaldehyde from biomass. Highlights: Hydrocracking and ionic liquids treatments reduce average molecular weight and β-O-4 linkages of Arabidopsis thaliana wild-type. Fewer differences were observed on Arabidopsis thaliana CAD mutant lignin after pretreatments application. (8-O-4), (8-5), and (8-8) linkages observed in CAD mutant make lignin more resilient to pretreatment than WT lignin. Hydrocracking allow to extract valuable aldehyde monomers from Arabidopsis WT and CAD lignin.